How migrants’ transcultural perceptions shape their children’s bilingual language development: Insights from a cross-sectional multicultural study - Caroline Barry; Charlène Mafuta; Hawa Camara; Bruno Falissard; Muriel Bossuroy; Marie Rose Moro; Amalini Simon; Dalila Rezzoug (PLoS ONE, 2025)
Background Little is known about the factors affecting children’s language acquisition in transcultural situations and how clinicians can take these children’s specific needs into account. Objectives To better understand the acquisition of bilingualism by migrant parents’ children, our aim was to study the relations between parental transcultural perceptions and their children’s language skills in both the heritage language and the host country’s majority language. Methods This cross-sectional study included 114 kindergarten children, born in France to migrant parents speaking Arabic, Tamil, or Soninke. Children’s expressive language and comprehension skills were assessed with the ELAL and the N-EEL scales. In semistructured interviews, parents answered questions about perceptions of migration-related changes, extended-family relationships, and transgenerational transmission. Quantitizing methods and regression models were used to assess these factors’ potential associations with children’s language skills after adjustment for background characteristics and languages used at home. Results Children of parents with a strongly positive perception of transgenerational transmission had better expressive skills in their heritage language. However, strongly positive parental perceptions of extended-family relationships and of migration-related changes were independently associated with some poorer skills in the heritage language. None of these transcultural/familial factors was significantly associated with any of the majority language skills assessed. Conclusion This research suggests that parental perceptions of migration, extended-family relationships, and transgenerational transmission are closely related to their children’s heritage language skills regardless of the choice of languages spoken at home. Further research on transcultural factors is necessary to illuminate the mechanisms underlying bilingual learning and inform evidence-based practices for clinicians.